Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2012
DOI: 10.1145/2207676.2207718
|View full text |Cite
|
Sign up to set email alerts
|

Looking glass

Abstract: In this paper we present our findings from a lab and a field study investigating how passers-by notice the interactivity of public displays. We designed an interactive installation that uses visual feedback to the incidental movements of passersby to communicate its interactivity. The lab study reveals:(1) Mirrored user silhouettes and images are more effective than avatar-like representations. (2) It takes time to notice the interactivity (approximately 1.2s). In the field study, three displays were installed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(93 citation statements)
references
References 23 publications
4
89
0
Order By: Relevance
“…As a result, the reading model is further explained, aiming at the characteristics of digital reading (Jacucci et al, 2010), as (1)traditional publishing model being challenged, (2)changes of readers' reading models, (3)interactive experiences in reading, and (4)far-reaching reading activity. Müller et al (2012) pointed out the key factors of media combination, digital reading characteristics, and digital reading devices in readers' electronic media reading processes.…”
Section: Digital Readingmentioning
confidence: 99%
“…As a result, the reading model is further explained, aiming at the characteristics of digital reading (Jacucci et al, 2010), as (1)traditional publishing model being challenged, (2)changes of readers' reading models, (3)interactive experiences in reading, and (4)far-reaching reading activity. Müller et al (2012) pointed out the key factors of media combination, digital reading characteristics, and digital reading devices in readers' electronic media reading processes.…”
Section: Digital Readingmentioning
confidence: 99%
“…This can be in contrast with installations to public urban spaces, where the attention seeking aspect may be based on deliberate disruption of conventions and routines [23].…”
Section: Impact On the Community's Activitiesmentioning
confidence: 99%
“…1-a. Its simple user interface was inspired by previous research that showed that passers-by do not spend a lot of time looking at public displays [7] and that live video feed represent a good mean for getting their attention [14]. For this reason we show a live video feed (1 in Fig.…”
Section: The Moment Machinementioning
confidence: 99%